HUBUNGAN LAMA KERJASAMA TERHADAP KEPERCAYAAN PELANGGAN PBF BINA PRIMA SEJATI - Brahmono, Umul Angga; Saragi, Sahat; Andayani, Nurita (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
The large number of pharmacies is not proportional to the number of PBF in DKI Jakarta, causing intense competition in drug distribution activities to pharmacies. The main concept of partnership or cooperation with customers is trust. Building trust will have an impact on bringing loyalty to continue working with the company. This study aims to determine the effect of the length of cooperation between PBF and pharmacies on customer trust. This research was conducted by survey and observation methods. The sampling technique was carried out by Probability Sampling with a Proportionate Stratified Random Sampling approach in order to obtain 69 pharmacies. The results showed that the length of cooperation from 69 pharmacies was 7-12 months for 1 pharmacy, 13-24 months for 8 pharmacies and >24 months for 60 pharmacies. The highest pharmacy confidence level is 85.51%, moderate is 13.04% and low is 1.45%. Based on the results of the Pearson correlation test, a sig value of >0.05 indicates that there is no relationship between length of cooperation and customer trust in PBF. This shows that there is no relationship between the length of time of cooperation with the level of trust the Pharmacy has in PBF Bina Prima Sejati.